The Influence of Self-Regulated Learning on Mastery of Fiqh Material among MA Al-Khairat Buntulia Students in Pohuwato Regency - Sriyana Mohi; Lian G. Otaya; Syahrial Labaso; Nurkholis Majid (Global Action and Education for Society, 2026)
This study aims to determine the effect of self-regulated learning on the mastery of fiqh material among students of MA Al-Khairat Buntulia, Pohuwato Regency. The research uses a quantitative approach with a simple linear regression method. The research population consisted of 53 students from grades X and XI, all of whom were sampled using the total sampling technique. Data collection was carried out using questionnaires, observations, documentation, and tests of mastery of fiqh material. Data were analyzed thru normality tests, linearity tests, t-tests, and the coefficient of determination (R²). The research results show that self-regulated learning has a positive and significant effect on students' mastery of fiqh material. This is evidenced by a significance value of 0.000 (< 0.05) and a regression coefficient value of 0.410. Additionally, the coefficient of determination (R²) value of 0.230 indicates that self-regulated learning contributes 23% to the mastery of fiqh material, while the remaining percentage is influenced by other factors outside the study. These findings indicate that the higher the students' ability to regulate and manage their learning process, the better their mastery of fiqh material. Therefore, the development of self-regulated learning needs to be given attention in the process of fiqh learning to optimally improve students' learning outcomes.